Management of Educational Infrastructure in Improving Human Resources Quality (Case Study at SMK Negeri 1 OKU) - Lukman, Lukman; Arafat, Yasir; Destiniar, Destiniar (Jurnal Pendidikan Tambusai, 2021)
This study aims to reveal more clearly about the management of educational facilities and infrastructure in improving the quality of human resources at SMK Negeri 1 OKU. This research is a qualitative research . This type of research is a case study research which means the real situation. The method used is descriptive analysis. Data were collected through observation, interview and documentation techniques. Based on the research results, it is concluded that the management of infrastructure facilities at SMK Negeri 1 OKU has been fulfilled by means of planning needs, procurement, inventory, maintenance and deletion